YIELD, ENERGY AND ECONOMIC ANALYSIS OF GREENHOUSE CUCUMBER (CUCUMIS SATIVUS L.) PRODUCTION UNDER DIFFERENT FARMING TREATMENTS - A. Zhanbota; R. S. Noor; G. Y. Wang; 4 (Journal of Animal and Plant Sciences, 2020)
Agrochemical based agriculture production is neither sustainable nor eco-friendly. A cost effective and sustainable organic farming is the need of time for better yield and quality. The efficient use of energy inputs improves productivity, profitability and economy. In this regard, we carried out this research for greenhouse hybrid cucumber (Kalam F1) production at Institute of Hydroponic Agriculture, Rawalpindi for the year 2017 to 2019 cropping season. The main objective was to evaluate the yield, energy and economic feasibility of greenhouse cucumber production under different farming treatments such as inorganic, organic and integrated fertilization application. The analysis was carried out based on energy use efficiency, energy productivity, benefits to cost ratio and amount of renewable and nonrenewable energies. The obtained results depicted that the total energy inputs for inorganic, organic and integrated greenhouse productions were 45856.3, 42945.3 and 54070.0 MJ ha−1, respectively. Energy use efficiency was 4.19, 4.84 and 4.87 while the energy productivity was 1.25 kg MJ−1, 1.26 kg MJ−1 and 1.40 kg MJ−1 under inorganic, organic and integrated fertilizer treatments, respectively. The average percentages of direct, indirect, renewable and non-renewable energies were 11%, 32.9%, 11.7% and 32.2% of the total energy, respectively. The net return of integrated farming treatment was highest (43135.60 $ ha−1) than organic (23555.33 $ ha−1) and inorganic (25127.93 $ ha−1) farming treatments. Similarly, the benefit to cost ratio were 7.75, 6.03 and 6.57, respectively from integrated to inorganic farming treatments. According to results, greenhouse cucumber production under integrated treatment showed high energy use efficiency, energy productivity, net return and benefit to cost ratio in comparison with organic and inorganic treatments which proved to be profitable practice for greenhouse cucumber production than organic and inorganic farming treatments.
Keywords: Greenhouse production; Cucumber; Organic farming; Energy analysis; Profitability